Biofertilizer increases the production and yield of sunflower (Helianthus annuus L.) oil in soils with adequate water availability - Barbosa, Marcelo de Andrade [UNESP]; Dantas, Geffson de Figueredo [UNESP]; Ferraz, Rener Luciano de Souza; de Mesquita, Evandro Franklin; Sá, Francisco Vanies da Silva; de Melo, Alberto Soares (Southern Cross Publishing, 2018)
The experiment was carried out with the goal of evaluating the productive aspects of sunflower cultivar Helium 253, in response to the application of cattle biofertilizer and levels of water availability in two types of soils. A completely randomized experimental design was adopted using the factorial 2×2×5 for the 2 types of soils: Entisol and Alfisol, two levels of water availability in the soil (100 and 50% of moisture retention capacity, and five rates of liquid cattle biofertilizer corresponding to 0; 0.75; 1.5; 2.25 and 3 L plant-1, prepared in the proportion of water 1:3. Sunflower plants were cultivated in pots with 30 L volume, individually filled with each type of soil, with daily water supply made based on humidity readings determined in the pots, using a capacitance multi-sensor probe type PR2/6 (Time Domain Reflectometry - TDR). To evaluate the sunflower production, the following variables were measured: internal diameter (IDH) and outer diameter of the head (ODH), number of seeds per plant (NSP), weight of 100 seeds (W100S) and oil content in seeds (OCS) and water consumption per plant (WCP). Among the studied soils, Entisol is the one that presents the best conditions for the production of the sunflower cv. Helium 253, being also the soil where the highest water consumption by plant occurs. For Entisol, it is recommended the rate of cattle biofertilizer estimated in 1.05 L plant-1, and for Alfisol the rate of 3 L plant-1. Regardless of the soil used, the highest production values are obtained when the soil was maintained with 100% of moisture retention capacity.
Keywords: Fertilization; Irrigation; Productivity